Peripheral cannabinoid 1 receptor blockade mitigates adipose tissue inflammation via NLRP3 inflammasome in mouse models of obesity - Han, Ji H.; Shin, Hanho; Rho, Jun G.; Kim, Jung Eun; Son, Dong H.; Yoon, Juhwan; Lee, Yong J.; Park, Jung Hyuck; Song, Byung J.; Choi, Chang Sik; Yoon, Seul G.; Kim, Il Y.; et al. (Diabetes, Obesity and Metabolism, 2018)
Aim: To analyze the metabolic parameters and adipose tissue inflammation via NLRP3 inflammasome following chronic treatment of mouse models of obesity with AJ5018 as the peripherally restricted cannabinoid 1 receptor (CB1R) antagonist. Materials and methods: The selectivity for CB1R over CB2R, brain/plasma concentration ratio, and centrally mediated neurobehavioural effects of AJ5018, were assessed. The long-term effects of AJ5018 and rimonabant on the metabolic parameters and adipose tissue inflammation were analyzed in diet-induced obese (DIO) mice and diabetic db/db mice. Results: AJ5018 had a higher degree of selectivity for CB1R over CB2R and markedly reduced brain penetrance, as reflected by the lower brain/plasma concentration ratio and the attenuated centrally mediated neurobehavioural effects, compared with its brain-penetrant parent compound rimonabant. In DIO and db/db mice, AJ5018 exhibited comparable effects to rimonabant in improving metabolic abnormalities and suppressing macrophage infiltration into white adipose tissue, activation of the NLRP3 inflammasome, and production of proinflammatory cytokines. Conclusions: These results suggest that peripheral CB1R blockade improves obesity-induced insulin resistance by suppressing adipose tissue inflammation via the NLRP3 inflammasome.
Keywords: Adipose Tissue; Animals; Brain; Cannabinoid Receptor Antagonists; Diabetes Mellitus, Experimental; Inflammasomes; Inflammation; Insulin Resistance; Macrophages; Male; Mice; Mice, Obese; NLR Family, Pyrin Domain-Containing 3 Protein; Obesity; Rimonabant; adipose tissue inflammation; insulin resistance; obesity; peripheral cannabinoid 1 receptor